Membaca Reaksi Publik: Analisis Komentar Pada Video 'Kroni Prabowo' di YoutubeTempo.co - Pane, Ratri Khaidir; Hasrullah; Farid, Muhammad (Sarjana Terapan Prodi Humas dan Komunikasi Digital Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2025)
This study aims to analyze the public response to the video “Prabowo's Cronies in the Free Nutritious Meal Project (MBG)” uploaded on YouTube Tempo.co, with a focus on the toxicity of comments and sentiments formed in public discussions related to the video. The phenomenon of concern is how netizens respond to political content and government policies through comments on social media platforms, and how these reactions affect the formation of public opinion. The research method used is sentiment analysis by utilizing the Communalytic.org tool to analyze the comments contained in the video, measure the level of toxicity, and identify sentiment patterns that appear in the discussion. The results showed that although there was a significant spike in toxicity on April 20, 2025, most of the comments showed low levels of toxicity after that period. The categories of severe toxicity, identity attack, insult, and threat were recorded very little. In addition, analysis of the distribution of toxicity scores per day revealed that the toxicity effect tends to subside after an initial peak in interaction. These findings suggest that while these videos trigger strong emotional responses initially, their long-term effects on public opinion are likely to be limited. This research contributes to the understanding of how social media affects political dynamics and how citizens process information based on their prior knowledge and attitudes.